Heatwave induced health vulnerability assessment in Bangladesh - Maria Mehrin; Fatema Tuz Zuhra; Md Mafizur Rahman (Environmental Research: Health, 2025)
Heatwaves emerge as a substantial environmental hazard, posing a severe threat to public health, especially in the tropical countries of South Asia. Despite Bangladesh’s susceptibility to natural disasters, including unprecedented temperature surge, heat stress lacks official recognition as a disaster. This study aims to assess the spatial distribution of health vulnerability to heat waves at the district level in Bangladesh. Utilizing a framework incorporating exposure, sensitivity, and adaptive capacity, the vulnerability index score for each district was computed. The study selected indicators by first reviewing relevant literature to identify key factors contributing to vulnerability to heatwaves. The final selection of 14 indicators, three for exposure, seven for sensitivity, and four for adaptive capacity, was made independently by the authors after consulting with experts and considering data availability. The entropy weight method, known for its objectivity in decision-making, was applied to assign weights to each indicator. The results indicated that the southwestern region and a portion of the northwestern part of Bangladesh are particularly exposed to heatwaves, with Kurigram identified as the most sensitive to heat. This heightened sensitivity is driven by a high floating population density, significant engagement in agriculture, and high population density. The districts most susceptible to heatwaves due to a combination of high sensitivity and low adaptive capacity include Barisal, Lakshmipur, Kishoreganj, Narayanganj, Narsingdi, Tangail, Jamalpur, Netrakona, Sherpur, Naogaon, Dinajpur, Kurigram, and Rangpur. These areas are likely to face the greatest impact from future heatwaves. This research facilitates strategic resource allocation by by identifying vulnerable districts and offering insights into the underlying causes, thereby supporting policy development and fostering international collaboration.